Powdery mildew resistance of barley in Southern Dagestan - B. A. Batasheva; R. A. Abdullaev; O. N. Kovaleva; I. A. Zveinek; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. The most effective way of protecting crops from diseases and pests is the breeding and cultivation of resistant varieties. The hydrothermal regime in the southern plains of Dagestan favors damage to barley plants by the causative agent of powdery mildew. The high level of disease progress observed annually helps to reliably assess the resistance of collection accessions to the pathogen.Materials and methods. The research material included 1361 barley accessions (570 improved cultivars and 791 landraces) of different ecogeographic origin and growth habit. Field experiments were launched concurrently with winter sowing. Powdery mildew resistance was scored during the heading period and in the milk ripeness phase using a point scale. Each accession was assessed for at least three years.Results and conclusions. The results of a long-term study disclosed a significant intraspecific variability of barley collection accessions in their resistance to powdery mildew. A significant part of the studied barley accessions (63.1%) appeared susceptible to the pathogen. The occurrence frequency of disease-resistant accessions was 11.0%, while those with medium resistance reached 25.9%. Among the landraces, four resistant accessions from the Abyssinian, West Asian and Mediterranean centers of crop origin were identified. Seventeen barley varieties resistant to powdery mildew (predominantly originated from Western Europe) are recommended for use in breeding for immunity.